My asthma and me. Live history - Raquel Asunción Díaz Alonso; David Palacios Martínez; Pedro Adalia Serrano (Universidad de Alicante, 2015)
The asthma is a disease which is characterized by the intermittent airway obstruction to the air-flow. Its world prevalence ranges between 1-24%. It courses clinically with dyspnea, cough, wheezing and/or chest pain. The degree of adherence to the treatment and disease control are influenced by the acceptance of the disease by the patients, their knowledge about it, and their strategy of coping with the asthma. This paper aims to provide a holistic and interdisciplinary point of view of the disease. We have conducted an interview in depth and a history of life of Daniel, our informer. We have collected and interpreted his experience of the disease with biographic and descriptive characteristic.